Functional Transcomplementation between Wheat Dwarf Virus Strains in Wheat and Barley - Isabelle Abt; Marlène Souquet; Gersende Angot; Romain Mabon; Sylvie Dallot; Gaël Thébaud; Emmanuel Jacquot (Viruses, 2019)
Wheat dwarf virus, transmitted by the leafhopper Psammotettix alienus in a persistent, non-propagative manner, infects numerous species from the Poaceae family. Data associated with wheat dwarf virus (WDV) suggest that some isolates preferentially infect wheat while other preferentially infect barley. This allowed to define the wheat strain and the barley strain. There are contradictory results in the literature regarding the ability of each of these two strains to infect its non-preferred host. To improve knowledge on the interactions between WDV strains and barley and wheat, transmission experiments were carried out using barcoded P. alienus and an experimental design based on single/sequential acquisitions of WDV strains and on transmissions to wheat and barley. Results showed that (I) WDV strains are transmitted with similar efficiencies by P. alienus males, females and larvae, (II) WDV wheat and barley strains do not infect barley and wheat plants, respectively, and (III) a functional transcomplementation between the wheat and barley strains allows a mixed infection of barley and wheat. The described ability of each WDV strain to infect a non-host plant in the presence of the other viral strain must be considered to analyze data available on WDV host range.